Attitudes to prescriptivism: an introduction*. Issue 3 (2nd April 2016) - Straaijer, Robin
ABSTRACT: The articles in this special issue investigate norms and prescriptions about norms and prescriptions in various languages and cultures. They started as papers for a workshop called 'Attitudes to Prescriptivism', held in 2013 at Leiden University. The aim of the workshop was to discuss attitudes towards prescriptivism, primarily from the point of view of those at whom such actions are directed. The articles in this special issue show a variety of attitudes to prescriptivism and the setting of norms, and towards the norms themselves.